2005
DOI: 10.1111/j.1439-0418.2005.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Action of carbendazim on the development of Nosema bombycis Naegeli in silkworm Bombyx mori L.

Abstract: Carbendazim, a benzimidazole compound is effective in curing pebrine disease in silkworm, Bombyx mori, caused by Nosema bombycis, if treatment is given within 48 h post-infection or before the parasite establishes itself in the host tissue. Ultrastructural evidence of the action of carbendazim showed an adverse effect of the drug on both merogonic and sporogonic stages of the parasite in the midgut and silk gland of the silkworm. The drug caused elongation, vacuolation and depletion of cytoplasmic contents of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Hence, any molecule used for control of different pests in mulberry will have an impact on growth and productivity of silkworms. The toxic residue of insecticides may rupture the integument, cause complete cessation of feeding, stiffness in body resulting in 'S' or 'C' shaped larvae, vomiting and incomplete ecdysis [10] exhibited shrinkage of the body due to muscle contraction [11] upon feeding the leaves harvested from pesticide sprayed mulberry plot. Hence, a specific waiting period is suggested for safe use of such chemicals [12].…”
Section: Larval Mortality (%)mentioning
confidence: 99%
“…Hence, any molecule used for control of different pests in mulberry will have an impact on growth and productivity of silkworms. The toxic residue of insecticides may rupture the integument, cause complete cessation of feeding, stiffness in body resulting in 'S' or 'C' shaped larvae, vomiting and incomplete ecdysis [10] exhibited shrinkage of the body due to muscle contraction [11] upon feeding the leaves harvested from pesticide sprayed mulberry plot. Hence, a specific waiting period is suggested for safe use of such chemicals [12].…”
Section: Larval Mortality (%)mentioning
confidence: 99%
“…Many studies suggest that benomyl and its derivative compounds are effective in controlling microsporidiosis in insects such as Nosema heliothidis in Heliothis zea and Nosema kingi in Drosophila willistoni ( Armstrong, 1976 ; Brooks et al, 1978 ). Ultrastructural evidence suggested that carbendazim causes elongation, vacuolation, and depletion of cytoplasmic contents of the of N. bombycis in meront and spore stages ( Jyothi et al, 2005 ). In China, carbendazim formulations have been registered and commercially marketed to control N. bombycis in silkworm seed production.…”
Section: Current Microsporidian Therapies and Their Targetsmentioning
confidence: 99%
“…For example, albendazole has been shown to be effective against several human pathogens, and fumagillin is applied to protect honeybees from Nosema apis infection [ 28 ]. A carbendazim-based formulation is also used to prevent N. bombycis infection in silkworm seed production [ 29 ]. An informative paper has recently been published on the treatment of honeybee nosemosis with antibiotics, small organic molecules, extracts and natural compounds [ 30 ].…”
Section: Introductionmentioning
confidence: 99%